Exercise motivation mediates individual and work determinants of sport participation among indonesian civil servants: a path analysis - Sepri Putra Anggara; Alnedral Alnedral; Asep Sujana Wahyuri; Roma Irawan; Ardo Okilanda (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
Physical inactivity is a major modifiable risk factor for non-communicable diseases, while evidence explaining how individual and workplace factors relate to sport participation among public-sector employees in low- and middle-income countries remains limited. This study examined the associations between individual factors, work factors, exercise motivation, and sport participation among Indonesian civil servants using a cross-sectional survey. A total of 426 eligible civil servants with at least one year of service voluntarily participated through purposive sampling, providing a sample adequate for the proposed path analysis. Four validated Likert-scale instruments (53 retained items; Cronbach’s α = .651–.902) measured the study constructs. Path analysis based on ordinary least squares regression was performed after all statistical assumptions were satisfied. Exercise motivation showed the strongest direct association with sport participation (β = .522, p < .001), followed by individual factors (β = .251, p < .001) and work factors (β = .089, p = .010). Individual factors demonstrated a stronger indirect association with sport participation through exercise motivation (.313) than their direct association (.251), whereas work factors showed a relatively small indirect association (.063). Together, the predictors explained 54.9% of the variance in sport participation (R² = .549). Because the study employed a cross-sectional design, the identified pathways should be interpreted as statistical associations rather than causal relationships. The findings highlight exercise motivation as the strongest correlate of sport participation and suggest that workplace health promotion should prioritize motivational strategies alongside supportive organizational environments.